2015
DOI: 10.1002/dvg.22859
|View full text |Cite
|
Sign up to set email alerts
|

A Hoxa13:Cre mouse strain for conditional gene manipulation in developing limb, hindgut, and urogenital system

Abstract: SUMMARYThe developing limb is a useful model for studying organogenesis and developmental processes. Although Cre alleles exist for conditional loss-or gain-of-function in limbs, Cre alleles targeting specific limb subdomains are desirable. Here we report on the generation of the Hoxa13:Cre line, in which the Cre gene is inserted in the endogenous Hoxa13 gene. We provide evidence that the Cre is active in embryonic tissues/ regions where the endogenous Hoxa13 gene is expressed. Our results show that cells expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…To understand why proximal (HH24) and distal (HH27) autopod progenitors show an equivalent PD potential when placed in an HH20 environment, we analysed the dynamics of expression of Hoxa13, the best marker of the autopod (Scotti et al, 2015;Tabin and Wolpert, 2007), in heterochronic grafts. In the chick wing bud, Hoxa13 expression is initiated at HH22 in an intrinsically timed manner and continues to be expressed through development, at least until day 10 (Saiz- Lopez et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…To understand why proximal (HH24) and distal (HH27) autopod progenitors show an equivalent PD potential when placed in an HH20 environment, we analysed the dynamics of expression of Hoxa13, the best marker of the autopod (Scotti et al, 2015;Tabin and Wolpert, 2007), in heterochronic grafts. In the chick wing bud, Hoxa13 expression is initiated at HH22 in an intrinsically timed manner and continues to be expressed through development, at least until day 10 (Saiz- Lopez et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Alox5 was the only exception because it was exclusively upregulated in RARβ antagonized limbs (LE135 versus DMSO +1.55-fold; RA versus DMSO −1.17). Seven of the 13 genes downregulated in RA-treated limbs are known to be expressed in the distal portion of the developing or regenerating vertebrate limb including Lhx9 (Gu and Kania, 2010;Tzchori et al, 2009), Zic5 (Merzdorf, 2007), Lmo1 (Taher et al, 2011), Lhx2 (Taher et al, 2011;Tzchori et al, 2009), Spry1 (Minowada et al, 1999;Wang and Beck, 2014), Msx2 (Bell et al, 2003;Carlson et al, 1998;Tribioli et al, 2002), HoxA13 (Gardiner et al, 1995;Haack and Gruss, 1993;Scotti et al, 2015), most of which are required for distal identity in developing mouse limbs. This suggests that distal-identity genes are silenced only in limbs undergoing PD duplication, similar to the transcriptional activation of proximalidentity genes during PD duplication.…”
Section: Gene Transcriptional Responses Associated With Ra-induced Prmentioning
confidence: 99%
“…These results suggested that Ihh is downstream (and could be a mediator) of androgen and estrogen signaling during sexual differentiation of the external genitalia. To test whether Ihh plays a role in masculinization of the penis, we knocked out Ihh in the mouse genital tubercle using Hoxa13Cre, which shows widespread expression in the external genitalia, including the urethral epithelium (42). Conditional deletion of Ihh by Hoxa13Cre led to underdevelopment of the penis and reduction of male-specific features, including the MUMP and the MUMP ridge, indicating an essential role for IHH in masculinization of mouse external genitalia (Fig.…”
Section: Ar and Erα Regulate Sex-specific Gene Expression In Externalmentioning
confidence: 99%